A review of research in applied linguistics published in New Zealand (2013–2017). (April 2020) - Skyrme, Gillian; Ker, Alastair
Abstract: This article presents selected research on applied linguistics published in New Zealand, following Language Teaching 's commitment to showcase more broadly local research that would not otherwise be easily accessible to an international audience. It covers research conducted and published in New Zealand from 2013 to 2017, following on from Ker, Adams, and Skyrme (2013). It begins with an overview of the language situation in New Zealand, then summarises research into language learning, teaching and use which has appeared in the domestic applied linguistics literature in the period. The review indicates the continuing depth and breadth of research activity in New Zealand. Major themes include the maintenance of languages other than English, notably the official languages, te reo Māori (the Māori language) and New Zealand Sign Language (NZSL), and strategies to reverse dwindling enrolments in courses in additional languages against the background of growing linguistic diversity. There is interest in innovative methodology, and in processes of assessment and curriculum development to underpin teaching in formal educational settings. The prevalence of studies with a focus on small numbers of cases reflects the preponderance of practitioner-led research. There is, however, a parallel trend towards larger-scale studies indicating capacity to undertake larger, collaborative projects.